EuReCa_Serbia 2014-2023 - Analysis of data on non-start of CPR in relation to time of day - Bandulaja, Marina; Susković Bosancic, Rajka; Medic, Sara; Vasilic, Milica; Ristic, Jovana (Journal Resuscitatio Balcanica, 2024)
Abstract Aim: The aim of this study was to determine a potential difference in the initiation of cardiopulmonary resuscitation (CPR) based on the period of the day. The reason for this lies in the results of a few studies which implied that there is a significant difference in survival rates after day and night out of hospital cardiac arrest (OHCA). Material and methods: This study analyzed epidemiological data on OHCA from the EuReCa study, collected via the European Resuscitation Council (ERC) EuReCa ONE protocol. The dataset, covering October 1, 2014, to December 31, 2021, was created using data from 16 municipalities in Serbia, representing 24.13% of the population. Results: During the period 2014-2023 year, 10458 cases of OHCA were identified via EuReCa Serbia programme. In 4261 out of those 10458 cases (40,7%) CPR was initiated by a witness or an ambulance, and it remained uninitiated in 6192/10458 (59,2%) cases. After splitting one day into four 6-hours periods, we have noticed a statistically significant difference in the proportion of initiated vs. uninitiated CPR according to the period of the day. The biggest proportion of uninitiated CPR cases occurred during the period of 6 to 12 o’clock 2177/3440 (63,3%), while the smallest proportion happend between 18 and 24 o’clock 1251/2332 (53,6%). When looking into the connection between days in the week and working days comparing to weekend, we haven’t established a statistically significant difference. Nevertheless, we did find one when investigating the proportion of initiated CPR cases compared to the season of the year. Conclusion: The proportion of initiated CPR cases is below the European average. We have concluded a statistically significant difference in the proportion of initiated vs. uninitiated CPR according to the period of the day. The biggest proportion of uninitiated CPR cases occurred during the period of 6 to 12 o’clock which is also the period with the highest frequency of OHCA. It is encouraging that despite many authors describing a lower survival rate after a night OHCA, we have found that the highest proportion of initiated CPR cases occurred during the night.